Marés internas e dinâmica sedimentar na plataforma continental amazônica - Molinas, Ernesto (2020)
The description of hydrodynamics associated to the extensive reef system on the shelf break adjacent to the Amazon River is still a challenge for ocean sciences. Despite the discharge of more than one billion tons of cohesive sediment per year, the outer continental shelf of the world’s largest river presents very low concentrations of suspended sediment near the bottom and absence of modern fine sediment deposits more than one hundred kilometers before the shelf break. The offshore limit of the subaqueous delta consists in a sigmoidal clinoform standing between 40- and 70-m depth, a depositional feature that cannot be explained solely by estuarine like gravitational circulation. This paper aims to test the hypothesis that internal tides have a major role on the control of offshore fine sediment transport. For that, we implement a set of tridimensional, non-hydrostatic and high-resolution (up to 2 m, vertical, and 2 km, horizontal) Delft3D models. The experiments showed that even disregarding river plume buoyancy, wind drag, superficial waves and ocean currents, the exclusive interaction between barotropic tidal currents, bathymetry and the stratification structure of the ocean can generate current asymmetry patterns compatible with modern deposition. The maximum shelf slope and the relative depth between the outer shelf and the pycnocline represent the main factors influencing generation and shoreward propagation of internal tides. In a temporal perspective, spring-neap cycles are eventually capable of reverting cross-shore subtidal transport tendencies, while seasonal variability of ocean stratification modulates the intensity of baroclinic processes.